1973
DOI: 10.1530/acta.0.0720545
|View full text |Cite
|
Sign up to set email alerts
|

BIOSYNTHESIS OF 11β-Hydroxyandrostenedione BY HUMAN AND BABOON ADRENALS

Abstract: The conversion of androstenedione and cortisol to 11β-hydroxyandrostenedione was studied by in vitro incubations of human and baboon adrenals and by in vivo perfusion of baboon adrenals. By both approaches, androstenedione appeared to be the major precursor. Some sidechain cleavage of cortisol also occurs during incubation with whole blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The levels of 11 β OHA, a rarely assayed androgen that originates mainly from 11 β -hydroxylation of A [ 29 ], showed a very close correlation with levels of A ( r s = 0.993). Given that 11 β OHA is also produced from cortisol [ 30 ], we suggest that 21DF may also contribute to the formation of this 11 β -hydroxylated androgen in CAH21.…”
Section: Discussionmentioning
confidence: 98%
“…The levels of 11 β OHA, a rarely assayed androgen that originates mainly from 11 β -hydroxylation of A [ 29 ], showed a very close correlation with levels of A ( r s = 0.993). Given that 11 β OHA is also produced from cortisol [ 30 ], we suggest that 21DF may also contribute to the formation of this 11 β -hydroxylated androgen in CAH21.…”
Section: Discussionmentioning
confidence: 98%
“…The synthesis of 11OHAD occurs predominately in the adrenal gland from AD (Figure 1), through the action of steroid 11β-hydroxylase (CYP11B1), and small amounts might be produced from cortisol 24 . Consistent with previous reports that measured only 11OHAD 25, 26 , we found negligible amounts of all 11oxC19 steroids in sera from patients with 11OHD, which confirms that their synthesis relies on CYP11B1.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of 21deoxycortisol(21DF) in response to ACTH has been advocated by a number of authors (Franks, 1974;Milewicz et al, 1984) as a more sensitive marker of the heterozygote state than the response of 17~-OH-progesterone (1 7Po). What these authors do not draw out is the particular significance of 21DF as the I ID-hydroxylated metabolite of 17Po which, in women with normal ovaries, almost certainly represents a pure adrenal compound, since very little I 10-hydroxylase activity is found in normal ovarian tissue (Axelrod et al, 1973). There is a suggestion, however, that polycystic ovaries may have some intrinsic 1 IB-hydroxylase activity (Maschler et af., 1975;Polson et al, 1986;Owen et al, 1988), while inhibition of 1 10-hydroxylation by androgen has been previously demonstrated (Baird et al, 1983).…”
Section: Discussionmentioning
confidence: 99%